Формування готовності майбутніх офіцерів до застосування протитанкового ракетного комплексу “Стугна-П” у різних умовах службово-бойової діяльності - Пістряк, П. В.; Pistriak, P. V.; Бєлашов, Ю. О.; Bielashov, Yu. O.; Самсонова, Г. С.; Samsonova, H. S.; Шабатура, С. О.; Shabatura, S. O.; Мартиненко, О. М.; Martynenko, O. M.; ORCID: https://orcid.org/0000-0002-9380-1442 (Науковий часопис НПУ імені М. П. Драгоманова. Серія 5: Педагогічні науки: реалії та перспективи. - 2022. - Вип. 90. - С. 107-113, 2022)
Апробовано педагогічні умови формування готовності майбутніх офіцерів Національної гвардії України до застосування протитанкового ракетного комплексу “Стугна-П” у різних умовах службово-бойової діяльності. З’ясовано, що в ході педагогічного експерименту значним чином зменшилася кількість курсантів Ег із низьким рівнем сформованості готовності до застосування ПТРК “Стугна-П” у різних умовах службово-бойової діяльності на 30,36%, водночас збільшилася кількість курсантів, які мають дуже високий рівень сформованості готовності до дій у складі бойових розрахунків ПТРК “Стугна-П” на 10,71%. У респондентів Кг зазначені вище зміни виражені несуттєво. Результати дослідження впровадженно у систему вогневої підготовки курсантів вищих військових навчальних закладів Національної гвардії України.

Formation of the readiness of future officers to use the anti-tank missile complex "Stugna-P" in various conditions of service and combat activity Summarizing the results of the analysis of scientific-methodical, special and reference literature, the members of the research group established, that the issue of developing and approving pedagogical conditions for the formation of the readiness of future officers of institutions of the security and defense sector of Ukraine for the use of the latest models of high-precision weapons in various conditions of official and combat activity is devoted to an insufficient number of scientific and methodological works, this requires further scientific investigations and emphasizes the relevance and practical component of the chosen research direction. The main goal of the study is the approbation of pedagogical conditions for the formation of the readiness of future officers of the National Guard of Ukraine to use the anti-tank missile complex "Stugna-P" in various conditions of service and combat activity. During the research and analytical work, the following research methods were used: abstraction, analysis and synthesis, induction and deduction, modeling, mathematical and statistical (correlation analysis, factor analysis), etc. As a result of an empirical study, the members of the research group (RG) tested the pedagogical conditions for the formation of the readiness of future officers of the National Guard of Ukraine (NGU) to use the anti-tank missile complex (ATMC) "Stugna-P" in various conditions of service-combat activity (SCA). The pedagogical conditions offered by us consist of the following blocks: diagnostic and organizational, formative and control. The introduction of the proposed pedagogical conditions into the system of fire training contributed to the improvement of the professional level (professional competences) of scientific and pedagogical workers who participated in the study (within the scientific project "Practice", 2021-2022). In addition, analyzing the obtained results, it is appropriate to state that the representatives of the experimental group have better indicators of the formation of theoretical knowledge of the structure and operation of the ATMC "Stugna-P", as well as its foreign analogues. Comparing the indicators of the practical implementation of the standards, which provide for educational and training (combat) launches using the ATMC "Stugna-P" by the members of the RG, an increase in the effectiveness of tactical thinking is noted among the representatives of combat calculations from the number of cadets of the experimental group (Eg), in contrast to the studied cadets of the control group (Kg). Members of the RG found out that during the pedagogical experiment, the number of Eg cadets with a low level of readiness for the use of ATMC "Stugna-P" in various SCA conditions significantly decreased by 30.36%, while at the same time, the number of cadets with a very high level increased formation of readiness for action as part of combat calculations of ATMC "Stugna-P" by 10.71%. Among the respondents of Kg, the above-mentioned changes are expressed insignificantly. Prospects for further research in the chosen direction of scientific intelligence involve the determination of the essential characteristics of the formation of the readiness of future officers of the institutions of the security and defense sector of Ukraine to throw hand grenades for range and accuracy in extreme SCA conditions.

Апробированы педагогические условия формирования готовности будущих офицеров Национальной гвардии Украины к применению противотанкового ракетного комплекса "Стугна-П" в различных условиях служебно-боевой деятельности.
The results of the research and experimental verification of pedagogical conditions for the formation of the readiness of future officers of the NGU to use the anti-tank missile complex "Stugna-P" in various conditions of service and combat activity
Пістряк, П. В. Формування готовності майбутніх офіцерів до застосування протитанкового ракетного комплексу “Стугна-П” у різних умовах службово-бойової діяльності / Пістряк П. В., Бєлашов Ю. О., Самсонова Г. С., Шабатура С. О., Мартиненко О. М. // Науковий часопис НПУ імені М. П. Драгоманова. Серія 5: Педагогічні науки: реалії та перспективи. - 2022. - Вип. 90. - С. 107-113. - DOI: https://doi.org/10.31392/NPU-nc.series5.2022.90.22.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; педагогічні умови; pedagogical conditions; педагогические условия; спеціальна фізична підготовка; special physical training; специальная физическая подготовка; професійні компетентності; professional competences; профессиональные компетентности; високоточна зброя; high precision weapon; высокоточное оружие; готовність; readiness; готовность